PEREMPUAN DALAM LINTAS SEJARAH (Studi Atas Peran Publik Sahabiyah-Sahabiyah di Masa Rasulullah SAW) - Syamzan Syukur (MUWAZAH : jurnal kajian gender, 2014)
The tradition of pre-Islamic Arabian society known as the position of women as imperior. Prophet as a feminist fight for equality derarat (egalitarian) between men and women. The struggle of the Prophet raise the dignity of women is very opposite to trasidi Arab society. Many traditions and fi'li qauli recommending that treat women well. Even at the time of the Prophet women taking a role in the public sphere-sphere were previously considered taboo for women. As in politics known Aisha, Umm Salama, Safia Bint Abdul Muttalib and others, in the field of education known in economics Aisha and Khadija bint Khuwalid known.